2022
DOI: 10.1007/s00784-022-04691-8
|View full text |Cite
|
Sign up to set email alerts
|

Recession coverage using the modified coronally advanced tunnel and connective tissue graft with or without enamel matrix derivative: 5-year results of a randomised clinical trial

Abstract: Objectives To evaluate the 5-year results of single and multiple recession type (RT) 1 and 2 (Miller I to III) recessions treated with the modified coronally advanced tunnel (MCAT) and connective tissue graft (CTG) with or without an enamel matrix derivative (EMD). The main outcome variable was the stability of obtained root coverage from 6 months to 5 years. Materials and methods In 24 patients, both complete and mean root coverage (CRC and MRC) and gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In both case series included in the present review, it was not possible to determine whether HA affected root coverage. Notwithstanding, the RD in Guldener et al's study [29] was comparable to the results obtained in the study by Sculean et al [33] and Stähli et al [47]. On the other hand, Lanzrein et al [28] found higher RD values at follow-up compared to those observed by Górski et al [48].…”
Section: Discussionsupporting
confidence: 74%
“…In both case series included in the present review, it was not possible to determine whether HA affected root coverage. Notwithstanding, the RD in Guldener et al's study [29] was comparable to the results obtained in the study by Sculean et al [33] and Stähli et al [47]. On the other hand, Lanzrein et al [28] found higher RD values at follow-up compared to those observed by Górski et al [48].…”
Section: Discussionsupporting
confidence: 74%
“…Probing attachment level (mm) T0 , 1980). In that respect, CTGs have been used clinically to increase the width of KT (Edel, 1974;Stähli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, it had been previously established that the differentiation pattern of epithelialization is conditioned by the connective tissue originating from KT applied to the recipient site (Bernimoulin & Schroeder, 1980). In that respect, CTGs have been used clinically to increase the width of KT (Edel, 1974; Stähli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that some critical surgical maneuvers were crucial to the success of root coverage in this case series, mainly the innovative suture technique. Despite the high relevance of the suture, some previous studies did not detail address this procedure 18 , 19 , 20 , 21 . First, using suspending sutures, a fixed anchorage with coronal traction is used to stabilize the graft in the teeth positioned at the mesial and distal ends of the grafted area.…”
Section: Discussionmentioning
confidence: 99%